2010
DOI: 10.3109/09553002.2010.496029
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone radiation-induced free radical damage in the liver is inhibited by the antioxidants n-acetyl cysteine and epigallocatechin-gallate

Abstract: Mobile phone-like radiation induces oxidative damage and changes the activities of antioxidant enzymes in the liver. The adverse effect of RFR may be related to the duration of mobile phone use. NAC and EGCG protect the liver tissue against the RFR-induced oxidative damage and enhance antioxidant enzyme activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 55 publications
3
44
0
2
Order By: Relevance
“…Malondialdehyde level was found to be increased in various organs of animals exposed to MWs (19)(20)(21)24,25) including liver (22,26,27). Our results show as well, that MDA levelsare increased in liver tissue of rats exposed to microwaves after prolonged exposition period (40 and 60 days).…”
Section: Disscusionsupporting
confidence: 75%
See 1 more Smart Citation
“…Malondialdehyde level was found to be increased in various organs of animals exposed to MWs (19)(20)(21)24,25) including liver (22,26,27). Our results show as well, that MDA levelsare increased in liver tissue of rats exposed to microwaves after prolonged exposition period (40 and 60 days).…”
Section: Disscusionsupporting
confidence: 75%
“…It has been proved that oxidative stress develops in response to microwave radiation exposure (18)(19)(20)(21). Studies have also demonstrated that antioxidants such ascaffeic acid phenyl ester, n-acetyl cysteineandepigallocatechin-gallateprevent oxidative stress caused by microwave exposure inanimal liver (22,23).…”
Section: Disscusionmentioning
confidence: 99%
“…It has been observed that Wi-Fi and mobile phone-induced RF-EMR may cause oxidative kidney injury in new-born rats (23). Ozgur et al (25) reported that exposure to RF-EMR induces lipid peroxidation, accompanied by decreased activity of SOD, myeloperoxidase and glutathione peroxidase (GSH-Px) in the kidney of guinea pig. At this point; the major effect of antioxidants on human health occurs through their radical scavenging mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…At this point; the major effect of antioxidants on human health occurs through their radical scavenging mechanism. Increasing numbers of studies are focusing on the harmful effects of RF-EMR and on the use of antioxidants in order to minimize these (25). The most dramatic increase in lipid peroxidation and decrease in antioxidant levels of the RF-EMR exposed rats were observed in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…While ROS formation can regulate the cellular balance against the negative effects of EMF exposure, overproduction of ROS may cause cellular damage (Jajte et al, 2002;Akdag et al, 2007). It has been reported that following exposure to 930 MHz of RF radiations, increased ROS production can be observed (Oktem et al, 2005;Ozgur et al, 2010). The essential process of free radical damage is considered a lipid peroxidation.…”
Section: Disequilibrium Oxidative Stress Antioxidant Enzymes and Emmentioning
confidence: 98%